Serum PD-1 regulation and PD-1 expression of CD4+Foxp3+ regulatory T cells in patients in thyroid eye disease associated with immunosuppression treatment - Sakai, Atsushi; Tagami, Mizuki; Misawa, Norihiko; Haruna, Yusuke; Tomita, Mami; Honda, Shigeru (Frontiers in Ophthalmology, 2024)
PurposeThyroid eye disease (TED) primarily occurs in hyperthyroid patients, sometimes resulting in poor visual prognosis. Although other autoimmune diseases have been reported to be associated with serum programmed cell death 1 (PD-1), the relationship with TED remains unknown. This study investigated the relationship between TED and immune checkpoint molecules.MethodsSerum immune checkpoint molecules were measured in TED and control patient blood samples. In TED patients, blood samples were compared before and 6 months after steroid pulse treatment. Cytometry analysis was additionally performed in TED and control patients to compare the expression of (PD-1) of T cells.ResultsSerum concentrations of PD-1 in TED and control patients were 163.49 ± 79.01 (pg/mL) and 123.58 ± 46.61 (pg/mL) (P = 0.03). Serum PD-L1 concentration in TED was 157.89 ± 55.34 (pg/mL), while 152.58 ± 22.70 (pg/mL) in control patients (P = 0.92). For flow cytometry analysis, the mean fluorescence intensity (MFI) ratio of PD-1 in Foxp3high CD45RA- of the CD4+ T cells and CD127-CD25high of the CD4+ T cells were higher in TED versus control patients (P = 0.04, P = 0.02). There was also a higher percentage of PD-1 expressions on CD4+ T cells and Foxp3high CD45- T cells in TED patients versus that for control patients (P < 0.001, P = 0.003).ConclusionsPD-1 expression of CD4+Foxp3+ regulatory T cells appear to be associated with TED pathogenesis before and after treatment. Regulatory T cells expressed PD-1 have possibilities of clinical activity and autoimmune pathology of TED.